SITUATION OF THE GOVERNMENT-PRESS RELATIONS IN TURKEY (1918-1960) - Şerif DEMİR (Fırat University, 2019)
After the World War I that the Ottoman Empire actually ended, the occupation forces’ being effective in Istanbul had the most effect on mass media. As a result, a large majority of the press in Istanbul approached suspicious of the national struggle growing in Anatolia or looked cold. Istanbul government and occupation forces had a huge impact on determining the attitude of Istanbul Press. It was impossible to say that the press was free and independent. But in spite of all that negativeness, there were lots of courageous newspapers supporting the National Struggle. Closing of The Liberal Republican Party and getting the opposition media to be silenced, having a number of measures on the press with the outbreak of World War II were the negative effects of political developments on the media. A new dimension was brought to the relationship between the press and the government. Turkey was changing rapidly. While social and political structure were also changing, some media organs had difficulty in understanding that situation entirely. When they developed some policies against the government with various reasons, they were purged. The political normalization begun with the process of the multi-party political life in the history of the press since 1945 had the same effect on the press. Many new media organs were instituted just as many political parties were established. While the policy had been manipulating the media so far, the media tried to influence the policy from the that time. The press' realm of freedom expanded considerably with Multi-Party System. There was a great extent of relief in that period , which is not even possible to compare with that of single-party system period. Because of the fact that the politicians of that period knew that the press was a great power, they gave due importance to it.